Sturge - Weber Syndrome: A Glimpse into A Rare Clinical Diagnosis - Retno Jayantri Ketaren; Jacob Christian Cenadi (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2025)
Background: Sturge-Weber syndrome is a spectrum of neurocutaneous disorders characterized by angiomas involving the face, choroid, and leptomeninges. Patients present with the typical “port wine stain”, acute seizure onset, and increasing hemiparesis. Case: A 1-year-old female presented to the ED with a seizure that coincided with a fever. The patient had two generalized tonic-clonic seizures in a day, which lasted less than 5 minutes. Before this, the patient had a history of seizures that started at 6 months old. The patient had an erythematous patch covering the right side of her face, along with left-sided weakness and positive plantar reflex on the left foot. Head non-contrast MRI scan showed a hypointense lesion/blooming artifact in the right frontal lobe on T2FFE and a prominent vascular structure on the right frontal lobe, accompanied by the widening of multiple veins and sinuses. Discussion: Sturge-Weber syndrome is complete when both facial angioma and leptomeningeal involvement are present. Diagnosis is confirmed through clinical features, with seizures and hemiparesis correlating to imaging findings. In our patient’s case, a type I Sturge-Weber syndrome diagnosis was made. The patient was started on oral anticonvulsants and future controls. Conclusion: Sturge-Weber syndrome is a clinical syndrome with many neurological complications. The lack of specific treatment urges an early diagnosis, as it can affect the patient’s outcome.